Variation Pattern of the Stress-Strain Curve of Concrete under Multifactor Coupling - Haijian Xie; Henglin Lv (Advances in Civil Engineering)
The air shafts of coal mines contain solid, liquid, and gaseous substances that corrode concrete under conditions of relatively high temperature and humidity. The coupling of various factors decreases the concrete strength and thus the bearing capacity of the air shaft lining. In this study, concrete corrosion tests were carried out by simulating the complex environment of a coal mine air shaft lining to study the variation in the concrete stress-strain curve. For corroded concrete specimens subjected to very low stress, the microcracks and holes were closed, generating a large deformation, indicating severe concrete corrosion. The longer the corrosion time was, the gentler the initial slope of the curve. Finally, the uniaxial compression constitutive model of corroded concrete was established based on the Weibull distribution of three parameters, and the model curve was compared with the experimental curve. This model can not only predict the change of the stress-strain curve of high-strength concrete in a coal mine air shaft environment but also provide theoretical reference for the application of high-strength concrete in an air shaft environment.